Determinants of high-performance organizations in Africa: A conceptual framework and research propositions - Okechukwu Ethelbert Amah; Kabiru Oyetunde (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The purpose of this study was to develop a conceptual high-performance framework that can be used to gauge how organizations operating in Africa contribute to the sustainability of the continent. This is necessary because literature review showed that the definition of high-performance is contextually located. Also, it was identified that the drive for sustainability made it mandatory for high-performance in Africa to be gauged with the triple bottom line measure. The study argued that organizations operating in the continent should partly be held responsible for social and environmental sustainability in alignment with the United Nations goals on sustainability. Based on these, it was postulated that a mind-set change was expected from business leaders to help them recognize the need for the triple bottom line measure of performance. As good corporate citizens, organizations must work to achieve long-term sustainability for the continent and for themselves. Hence, a conceptual model for defining high-performance in the African context was developed along with research proposals for testing the model in future. The study concluded that the conceptual model would ensure that organizations in Africa operate in an ethical manner so as to enhance sustainability in Africa.
Keywords: D21; D23; L21; L23; 330; High-performance; triple bottom line; organizational strategy; sustainability; Africa